Improving The Reading Comprehension of The Eighth Grade Students of SMP Negeri 4 Parepare Through Cooperative Integrated Reading Composition (CIRC) Method - Suci Anugrah (La Parole : Journal of Language Teaching and Pedagogy, 2020)
The objective of the research is to find out whether or not the use of Cooperative Integrated Reading Composition (CIRC) method able to improve the students’ reading comprehension of the eighth grade students at SMP Negeri 4 Parepare The researcher applied quasi-experimental method, with two classess pretest and posttest design. The sample analysis consisted of 40 students from two classes. In the sampling process was taken cluster random sampling and this sample of this research took VIII.8 as experimental class with 20 students and VIII.7 as control class. The students given treatment with material about narrative text. The data were collected by using reading test. In experimental class through Cooperative Integrated Reading Composition (CIRC) method and control class through Discussion Conventional Method. The result of the data analysis showed that Cooperative Integrated Reading Composition (CIRC) method can improved the reading comprehension significantly. It was proved by the mean score on pretest was 55 and the posttest was 79. In addition, after analyzing the data by using the test formula, the result of t-test value is 2.654 and t-table value 1,685. It means that the t-test value was greater than t-table value (1.685). It indicated that H1 was accepted and H0 was rejected. Therefore, the hypothesis of the research is reading comprehension of the eighth year students at SMP Negeri 4 Parepare who are taught through Cooperative Integrated Reading Composition method is better than the students who are taught through Discussion Conventional Method